Duplex Interpenetrating-Phase FeNiZn and FeNi3 Heterostructure with Low-Gibbs Free Energy Interface Coupling for Highly Efficient Overall Water Splitting - Zhou, Qiuxia; Xu, Caixia; Hou, Jiagang; Ma, Wenqing; Jian, Tianzhen; Yan, Shishen; Liu, Hong (Nano-Micro Letters, 2023)
The sluggish kinetics of both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) generate the large overpotential in water electrolysis and thus high-cost hydrogen production. Here, multidimensional nanoporous interpenetrating-phase FeNiZn alloy and FeNi3 intermetallic heterostructure is in situ constructed on NiFe foam (FeNiZn/FeNi3@NiFe) by dealloying protocol. Coupling with the eminent synergism among specific constituents and the highly efficient mass transport from integrated porous backbone, FeNiZn/FeNi3@NiFe depicts exceptional bifunctional activities for water splitting with extremely low overpotentials toward OER and HER (η1000 = 367/245 mV) as well as the robust durability during the 400 h testing in alkaline solution. The as-built water electrolyzer with FeNiZn/FeNi3@NiFe as both anode and cathode exhibits record-high performances for sustainable hydrogen output in terms of much lower cell voltage of 1.759 and 1.919 V to deliver the current density of 500 and 1000 mA cm−2 as well long working lives. Density functional theory calculations disclose that the interface interaction between FeNiZn alloy and FeNi3 intermetallic generates the modulated electron structure state and optimized intermediate chemisorption, thus diminishing the energy barriers for hydrogen production in water splitting. With the merits of fine performances, scalable fabrication, and low cost, FeNiZn/FeNi3@NiFe holds prospective application potential as the bifunctional electrocatalyst for water splitting. Highlights: 1 Free-standing bimodal porous interpenetrating-phase FeNiZn and FeNi3 intermetallic heterostructure is in situ built on NiFe foam by dealloying way. 2 FeNiZn/FeNi3@NiFe exhibits superior electrocatalytic activities toward both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) with very low overpotentials and prolonged catalytic durability in alkaline medium. 3 The strong synergy between FeNiZn alloy and FeNi3 intermetallic generates modulated electron structure and thus well optimizes the intermediates chemisorption toward OER and HER.